Carcass and meat quality traits in Nellore and F1 Nellore-Araguaia crosses - Costa, N. V.; Aboujaoude, C. [UNESP]; Vieira, G. S.; Paiva, V. V.; Moraes Neto, R. A.; Gondim, V. S. [UNESP]; Alves, L. R.; Torres, M. C.L.; Antunes, R. C. (Genetics and Molecular Research, 2015)
We evaluated and compared carcass traits and meat quality in Nellore cattle and F1 crosses between Nellore and Araguaia, where 17 individuals were from the Nellore group and 19 were ½ Nellore and ½ Araguaia crosses. All animals belonged to the same birth season and were raised in pasture systems under the same nutritional, environmental, and management conditions. When the animals reached slaughter weight, they were taken to an industrial slaughterhouse where food was not provided for 24 h (free access to water); they were then stunned, bled, the leather was removed, and they were eviscerated. The carcasses were weighed (hot weight), kept in chilled storage for approximately 24 h at 4°C, and weighed again to obtain the chilled carcass weight. Carcass yield, carcass length, carcass width, leg length, thigh perimeter, loin eye area (LEA), retail cuts, cooling loss, pH, fat depth, marbling rate, intramuscular fat, color, and shear force were analyzed and sensory analysis of the meat was conducted. Significant differences (P < 0.05) were observed for the following variables: slaughter weight, hot and chilled carcass weights, carcass and leg lengths, thigh perimeter, LEA, retail cuts, and lightness (L*), where the ½ Nellore ½ Araguaia individuals showed higher means for all of these traits, except leg length and L*. Therefore, crossbreeding between Nellore and Araguaia did not affect the meat’s sensory characteristics, but contributed to an improvement in carcass traits, providing an alternative for farmers that aim for good meat quality, with a higher meat percentage.
Keywords: Bos indicus; Bos taurus; Loin eye area; Sensory analysis; Shear force; Slaughter weight